Treatment patterns for adrenal metastases using surgery and SABR during a 10-year period. (May 2022) - van Vliet, Claire; Dickhoff, Chris; Bahce, Idris; Engelsman, Anton F.; Hashemi, Sayed M.S.; Haasbeek, Cornelis J.A.; Bruynzeel, Anna M.E.; Palacios, Miguel A.; Becker-Commissaris, Annemarie; Slotman, Berend J.; Senan, Suresh; Schneiders, Famke L.
Abstract: We studied treatment patterns for adrenal metastases using surgery or SABR at a single institution during a 10-year period. The number of patients undergoing SABR doubled since 2016, without a change in numbers undergoing surgery. Both treatments resulted in low rates of acute toxicity and similar survivals.